O processo de invenção ficcional em Eles eram muitos cavalos, de Luiz Ruffato - Maciel, Maria Lucia (2015)
This dissertation examines the nonlinear narrative of the novel Eles eram muitos cavalos written by Luiz Ruffato. The main question concern to the analogy between the novel's verb-space structure and the art-installation. The focus is on specifics aspects of the novel, such as the distinctive creative process that, in turn, coadunate to performance and plasticity that are related to installation art. Ruffato's novel, which, as a heterogeneous work, does not follow the regular poetics' prerogatives. Instead, it is a new creative literary composition in which the author, the work, and the reader are imbricated, emerging out of this intransitive experience that requires from the reader a dispersive unfolding of the novel's structure. To understand a composition whose parts are disconnected, you must see this composition as an limite-experience, as limit in which interiority, subjectivization, desire and eroticism are involved as just the concept of "outside", which means an unstopped way to resignification their intensive and multiples means. Therefore, the theme is divided into three chapters through which we approach the novel's creation from its familiarity with the hypertext and the necessary "outside" experience. In other terms, the topic is addressed by the Ruffato's novel relationship with an art installation, especially by the concept of spatial performance that can or can not present the possibility of verisimilitude. Ultimately, we state on the novel spatial narrativity as intranscriptible realism unless by meaning is imposed by the aesthetic art experience provided by Eles eram muitos cavalos. From authors such as Heidegger, Bataille, and Blanchot, this paper tried to elucidate the dispositif poetics that are articulated and are articulators of a work that evoke the human totality only intelligible in the paradigm of contemporaneity